Oncofertility research pitfall? Recall bias in young adult cancer survivors - Esther H. Chung, M.D; Sloane Mebane, M.D; Benjamin S. Harris, M.D., M.P.H; Erin White, M.S; Kelly S. Acharya, M.D (Elsevier, 2023)
Objective: To assess recall bias by evaluating how well female cancer survivors remember details regarding their cancer diagnosis, treatment, and fertility preservation (FP) counseling.Oncofertility literature cites recall bias as a pitfall of retrospective surveys, but limited data exist to quantify this bias. Design: Retrospective secondary analysis of cross-sectional survey data. Setting: Single academic medical center. Patient(s): Female oncology patients of reproductive age, 18-44 years old, at least 6 months past their last chemotherapy treatment. Intervention(s): Not applicable. Main Outcome Measure(s): Recall of details surrounding cancer diagnosis and chemotherapy regimens, recall of FP counseling and ovarian reserve testing, and rates of chart-documented FP counseling. Result(s): In total, 117 patients completed the survey, with 112 verified via chart review. When asked to report the chemotherapy regimen, 57% (64 of the 112) marked "I don't know/prefer not to say." Regarding FP, 80% (90 of the 112) denied being offered counseling. Of the 37 (33%) who had documented FP conversations, 13 (35%) did not recall mention of fertility. Only 2 of 8 patients with ovarian reserve testing recalled this being performed at their initial visit. Multivariable logistic regression revealed older age was significantly associated with not being offered FP (odds ratio [OR] 0.87). Conclusion(s): Our results confirm that the accuracy of oncology patients' reporting is limited by a poor recall, particularly regarding their specific chemotherapy regimen. More than 1 in 3 patients documented to have been offered FP counseling do not recall this discussion. Importantly, only one-third of cancer survivors had chart-documented FP counseling. Increased efforts are needed to ensure adequate follow-up beyond the initial visit.